The Use and Relevance of Archaeological Open-Air Museums - Roeland Paardekooper (EXARC Journal)
Archaeological open-air museums form a colourful and varied assemblage of heritage institutions. These are places where stories about the past, inspired by archaeology, are presented. Their obvious use is for experimental archaeology, ancient crafts and live interpretation. However, these museums can be more relevant to society than meets the eye. They can teach newcomers about the past of their new habitation region; they can teach people fundamental learning in order to better cope with society and can show the big picture of environmental sustainability spanning millennia. Finally, archaeological open-air museums can teach their visitors a valuable lesson about political conscience and citizenship, including a debate on fake news. International cooperation is increasingly important for archaeological open-air museums and a necessity to survive and thrive. EXARC is an important network helping exactly with this. These museums need to improve, to believe in their strengths and unique selling points, and find new directions. A previous version of this article was published in German (Paardekooper, 2019).